Fabrication of Ag nanoparticle/ZnO thin films using dual-plasma-enhanced metal-organic chemical vapor deposition (DPEMOCVD) system incorporated with photoreduction method and its application. (January 2017) - Lei, Po-Hsun; Cheng, Chun-Han
Abstract: We report a novel method to grow silver nanoparticle/zinc oxide (Ag NP/ZnO) thin films using a dual-plasma-enhanced metal-organic chemical vapor deposition (DPEMOCVD) system incorporated with a photoreduction method. The crystalline quality, optical properties, and electrical characteristics of Ag NP/ZnO thin films depend on the AgNO3 concentration or Ag content and annealing temperature. Optimal Ag NP/ZnO thin films have been grown with a AgNO3 concentration of 0.12 M or 2.54 at%- Ag content and 500 °C- rapid thermal annealing (RTA); these films show orientation peaks of hexagonal-wurtzite-structured ZnO (002) and face-center-cubic-crystalline Ag (111), respectively. The transmittance and resistivity for optimal Ag NP/ZnO thin films are 85% and 6.9×10 −4 Ω cm. Some Ag NP/ZnO transparent conducting oxide (TCO) films were applied to InGaN/GaN LEDs as transparent conductive layers. The InGaN/GaN LEDs with optimal Ag NP/ZnO TCO films showed electric and optical performance levels similar to those of devices fabricated with indium tin oxide.